Self-Efficacy dan Kepuasan Kerja pada Guru Taman Kanak-Kanak (TK) - Hasanah, Nur; Laily, Nadhirotul (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this research is to find out the relathionship between self-efficacy and job satisfaction teacher at Preschool. This research is quantitative using correlation technique. The population is the teachers at Preschool ‘Aisyiyah Bustanul Athfal Gresik. Incidental sampling was used and 98 teachers have been selected as sample. The instrument was used by the reseachers were self-efficacy and job satisfaction scale. The correlation test result shows r = 0,127, p= 0,213 (p>0,05). Based on correlation test result, it can be consluded that Ha rejected and H0 accepted. There is no positive relationship between self-efficacy and job satisfaction teacher at Preschool.